2022
DOI: 10.21203/rs.3.rs-1700540/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fragility curves of masonry buildings in aggregate accounting for local mechanisms and site effects

Abstract: Masonry buildings in aggregate are largely diffused within the existing Italian and European building stock, especially in historical centres. Their seismic evaluation represents a difficult and open task that has not been exhaustively investigated so far. The study proposes a procedure aimed at evaluating the potential impact of the combination of local mechanisms and site-amplification in terms of fragility curves on an existing masonry aggregate. The latter consists of five adjacent structural units mutuall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore, the difficulty involved in adequately connecting the two construction systems underlies the fact that many buildings presented damage resulting from sliding between lower walls and upper floors of differing materials (Figure 15b). Additionally, the positioning of these dwellings within the aggregate might influence their seismic response [38][39][40].…”
Section: Structural Damage In Traditional Construction Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the difficulty involved in adequately connecting the two construction systems underlies the fact that many buildings presented damage resulting from sliding between lower walls and upper floors of differing materials (Figure 15b). Additionally, the positioning of these dwellings within the aggregate might influence their seismic response [38][39][40].…”
Section: Structural Damage In Traditional Construction Systemsmentioning
confidence: 99%
“…Previous seismic events and research into these events have shown the importance of the position in the block [40,[46][47][48][49][50] and the pounding effects [38,51] between adjacent buildings on the seismic vulnerability. The seismic performance of masonry building aggregates is often affected by the presence of fragile and deformable floor membranes, along with asymmetrical geometries.…”
Section: Urban Positionmentioning
confidence: 99%